Arts programming for the anthropocene art in community and environment - Gilbert, Bill 1950-; Cox, Anicca (Routledge environmental humanities, 2019)
"Arts Programming for the Anthropocene argues for a role for the arts as an engaged, professional practice in contemporary culture, charting the evolution of arts over the previous half century from a primarily solitary practice involved with its own internal dialogue to one actively seeking a larger discourse. The chapters investigate the origin and evolution of five academic field programs on three continents, mapping developments in field pedagogy in the arts over the past twenty years. Drawing upon the collective experience of artists and academicians in the United States, Australia, and Greece operating in a wide range of social and environmental contexts, it makes the case for the necessity of an update to ensure the real world relevance and applicability of tertiary arts education.